PENGARUH TRUST IN BRAND, BRAND IMAGE, DAN SERVICE QUALITY TERHADAP CONSUMER LOYALTY PADA PRODUK INDIHOME KOTA PANGKALPINANG - Siti Aisyah; Suhardi Suhardi; Rita Deseria (LPPM STIE PERTIBA Pangkalpinang, 2020)
Industrial revolution 4.0 brings markets that are more producer to consumers. In the past, consumers transacted through traditional or modern markets, in the digital era the market is brought closer to information technology so that producers can market their products directly. In this era, information technology has become the main engine so that data and information become an important weapon for companies to win the competition. This study aims to determine and analyze the effect of trust in a brand, brand image, and service quality on customer loyalty at IndiHome in Pangkalpinang city. This study involved 99 indiHome customers, the data collected was processed and analyzed using multiple regression models. The results of the study show that brand trust, brand image, and service quality on customer loyalty have a positive and significant effect on IndiHome products.